Concentrations of selected radionuclides and their spatial distribution in marine sediments from the northwestern Gulf, Kuwait. (February 2018) - Uddin, Saif; Behbehani, Montaha
Abstract: This study focuses on creating a baseline for 40 K, 210 Pb, 137 Cs, 90 Sr, 226 Ra, 228 Ra, 238 U, 235 U, 234 U, 239 + 240 Pu and 238 Pu in marine sediments in the northwestern Gulf. The respective measured concentration ranges were 386–489, 32.3–48.8, 1.5–2.9, 4.53–5.42, 18.3–23.1, 18.8–23.0, 22.3–30.5, 0.99–1.33, 25.6–34.8, 0.30–0.93, and 0.0008–0.00018 Bq kg − 1 . The levels of these radionuclides are generally comparable to values reported for other marine waters in the northern hemisphere. The 137 Cs activity in the Gulf sediments offshore Kuwait is an order of magnitude lower compared to sediments from northeastern Iran. Other than that finding, no hot spots were observed in sediments adjacent to power and desalination plants, oil and gas industrial activities or wastewater treatment facilities. These data will serve as a baseline to gauge possible future inputs of radionuclides in the northern Gulf. The calculated average ratio of 235 U/ 238 U activity in the area is in agreement with the reported figure of the natural uranium ratio, suggesting the absence of depleted uranium (DU) at all the stations. The low concentration of 239 + 240 Pu suggests that there is no significant source of plutonium except that from atmospheric fallout from weapon testing and possible dry deposition via long-range dust transport. Highlights: The study reports baseline concentrations of radionuclides in marine sediments Knowledge of radioactivity concentrations in marine sediment is critical to assess contamination from Oil industry and NPPs 235 U/ 238 U activity in the area suggests the absence of depleted uranium (DU) at the stations covered in this study 239 + 240 Pu concentration suggests that there is no significant source of plutonium except the atmospheric fallout There is no significant change in levels of some of the radionuclides in past two decades.